ANALISIS PERBANDINGAN METODE FIFO (First In First Out) DAN LIFO (Last In First Out) DALAM PENGENDALIAN INVENTORI PRODUK TEPUNG BUMBU SERBAGUNA PT XYZ - Mirza Rosa Labibah; Amalia Ma’rifatul M (CV. Denasya Smart Publisher, 2025)
This study was conducted through an internship at PT. XYZ, focusing on a comparative analysis of the First In, First Out (FIFO) and Last In, First Out (LIFO) inventory management methods for all-purpose flour. The background of this study is the company's need to manage inventory of perishable ingredients, so an effective inventory management strategy is needed to maintain product quality, achieve cost efficiency, and minimize the risk of quality deterioration. The study aims to analyze the impact of implementing FIFO and LIFO methods on inventory valuation, Cost of Goods Sold (COGS), and the resulting gross profit margin. The methods used include direct observation in the field, interviews with relevant parties, and analysis of the company's production and inventory data during the research period. The results of the study show that, although the physical quantity of inventory is the same for both FIFO and LIFO methods, there are significant differences in the ending inventory value and HPP, which then affect the gross profit margin. The FIFO method yields a higher ending inventory value and a lower HPP compared to the LIFO method, resulting in a higher gross profit and making it more suitable for perishable products. Based on these findings, the FIFO method is considered more optimal for implementation at PT. XYZ to increase cost efficiency, maintain product quality, and support the company's ongoing profitability.